STRATEGIES FOR STRENGTHENING CHARACTER NATIONALISM THROUGH THE MEDIUM OF NATIONAL ANTHEMS: A CASE STUDY OF THE MUHAMMADIYAH KEPONG GUIDANCE CENTER IN MALAYSIA - Juliaman Siahaan; Zulkifli Amin; Ryan Taufika; Cindy Safira; Heru Sanjaya; Miftha huljannah (Journal Analytica Islamica, 2026)
This study aims to analyze strategies for strengthening nationalism through the medium of national anthems among children at the Muhammadiyah Kepong Guidance Center in Malaysia. Nationalism is a fundamental value for Indonesian migrant workers' children living abroad who are vulnerable to national identity crises. The study uses a qualitative approach with a case study method. The research subjects consist of the center manager, homeroom teachers, and nine students. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model. The results of the study show that the strategy to strengthen nationalism is carried out through: (1) the habit of singing national songs before learning, (2) internalization of the meaning of song lyrics, (3) integration with history lessons, and (4) commemoration of national holidays. The implementation of these strategies effectively improved understanding of the nation's history, fostered love for the homeland, strengthened national identity, and shaped a disciplined character and a sense of pride as Indonesian citizens.